2005
DOI: 10.1200/jco.2004.12.027
|View full text |Cite|
|
Sign up to set email alerts
|

Weekly Epoetin Alfa Maintains Hemoglobin, Improves Quality of Life, and Reduces Transfusion in Breast Cancer Patients Receiving Chemotherapy

Abstract: Epoetin alfa administered at 40,000 U qw is effective in improving QOL, maintaining hemoglobin level, and reducing transfusion requirements in breast cancer patients. The high effectiveness observed could be attributed in part to early treatment with epoetin alfa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
90
0
8

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(102 citation statements)
references
References 16 publications
4
90
0
8
Order By: Relevance
“…Contrary to the higher early mortality seen in the BEST study, Chang et al [29] did not observe a shorter survival time in the ESA group of patients. In the Chang et al [29] study, the epoetin arm showed a similar 2-year survival rate and no difference in thromboses. The BRAVE study, in 463 metastatic breast cancer patients receiving chemotherapy (anthracycline and/or taxane based), compared once-weekly epoetin beta with control (transfusions allowed as clinically indicated in both arms) [24].…”
Section: Update Of Recent Breast and Cervical Cancer Clinical Studiesmentioning
confidence: 42%
See 2 more Smart Citations
“…Contrary to the higher early mortality seen in the BEST study, Chang et al [29] did not observe a shorter survival time in the ESA group of patients. In the Chang et al [29] study, the epoetin arm showed a similar 2-year survival rate and no difference in thromboses. The BRAVE study, in 463 metastatic breast cancer patients receiving chemotherapy (anthracycline and/or taxane based), compared once-weekly epoetin beta with control (transfusions allowed as clinically indicated in both arms) [24].…”
Section: Update Of Recent Breast and Cervical Cancer Clinical Studiesmentioning
confidence: 42%
“…A possible reason for the impaired survival seen with the ESA group in the BEST study in the first year of study (particularly in the first 4 months after randomization) may not have been a result of tumor progression, but possibly thromboembolic events. Chang et al [29] conducted a study in 354 breast cancer patients receiving chemotherapy, comparing once-weekly epoetin alfa with standard care. Contrary to the higher early mortality seen in the BEST study, Chang et al [29] did not observe a shorter survival time in the ESA group of patients.…”
Section: Update Of Recent Breast and Cervical Cancer Clinical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis of data from 15 randomized controlled trials of epoetin showed a consistently high rate of hematologic response, with an overall risk ratio of 3.42 (95% confidence interval [CI], 3.03-3.06) relative to control (Table 1) [13,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. The likelihood of Hb response is at least as large when the starting Hb level is 10-12 g/dl as it is when baseline Hb is <10 g/dl.…”
Section: Esasmentioning
confidence: 99%
“…Epoetin alfa therapy has been shown in both double-blind, placebo-controlled, and open-label studies to increase Hb levels in cancer patients receiving platinum-or nonplatinum-based chemotherapy, correcting anaemia, decreasing transfusion requirements, and subsequently improving patients' QOL (Abels, 1992;Leitgeb et al, 1994;Glaspy et al, 1997;Demetri et al, 1998;Dammacco et al, 2001;Gabrilove et al, 2001;Littlewood et al, 2001;Thomas, 2002;Janinis et al, 2003;Shasha et al, 2003;Savonije et al, 2004;Chang et al, 2005;Witzig et al, 2005). However, few studies to date have examined the outcome of anaemia treatment in ovarian cancer patients, and none have specifically evaluated the impact of anaemia treatment on QOL in this population (ten Bokkel Huinink et al, 1998).…”
mentioning
confidence: 99%